The consumption and use of wild foods by children across a deforestation gradient in Zomba District, Malawi - Maseko, Heather Nonhlanhla (Rhodes University, Faculty of Science, Department of Environmental Science, 2016)
Despite consensus on their significant nutritional value, wild foods are continually excluded from both food security statistics and economic values of natural resources. Though largely unexplored, there is evidence on the use of wild foods by children to supplement their diets and as a source of income. Children have knowledge on the gathering and hunting of selected wild food species and sources thereof. Wetlands, agro-ecosystems, natural forests, human landscapes and river systems remain important sources of wild food resources. The provision of and access to these resources are significantly affected by the interference and disruption to natural ecosystems. In Malawi, interference has been largely due to deforestation and land use change caused by an interplay of pressures from population growth for development and agricultural expansion. Against this background, the implications of deforestation and vegetation cover on the availability of wild foods and their access and use by children is largely unexplored. Through a comprehensive analysis of data collected from 150 children and 50 elderly men and women, the integration of Participatory Rural Appraisal (PRA) exercises and Geographic Information System (GIS), in the four sites of Mpheta, Mtuluma, Kasonga and Makombe in Zomba district, wild foods availability was established and their contribution to the nutritional status of children and households' food security assessed. Study sites were identified along the deforestation gradient of Lake Chilwa, Zomba Mountain and Shire River basin with an additional focus on varying landscapes. One hundred and twenty species of wild foods were identified with greatest availability in areas of high vegetation cover and the lowest in areas of low vegetation cover, but with meaningful differences per wild food category. There was considerable reduction in the availability of wild foods with increasing deforestation; mainly wild game and fruits species and, in turn, decreased access of these by children. Nevertheless, small game, insects, other wild fruits and wild vegetables thrive well in agro-ecosystems and therefore were minimally affected by deforestation but largely by management practices of those systems and can be possibly improved through the promotion of agro-ecological farming systems. The research reveals that wild foods form an important component of the starch based diets of households from agricultural communities in the various landscapes. Besides securing the household's food base, all children largely supplemented their diets with wild foods but with increased dependence by children from poorer households who are highly vulnerable to food insecurity. Access and use of wild foods was largely dependent on children's knowledge, perceptions of the wild food and ease of access, with considerable variations due to gender and socio-cultural norms. Besides contributing to the nutritional status and food security, commercialisation of wild foods was common among children, hence providing them with an alternative livelihood strategy and in some cases only viable source of income.
Keywords: Uncatalogued